2019
DOI: 10.1016/j.neurobiolaging.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Association of NIPA1 repeat expansions with amyotrophic lateral sclerosis in a large international cohort

Abstract: NIPA1 (non-imprinted in Prader-Willi/Angelman syndrome 1) mutations are known to cause Hereditary Spastic Paraplegia type 6, a neurodegenerative disease that phenotypically overlaps to some extent with Amyotrophic Lateral Sclerosis. Previously, a genome-wide screen for copy number variants found an association with rare deletions in NIPA1 and ALS, and subsequent genetic analyses revealed that long (or expanded) polyalanine repeats in NIPA1 convey increased ALS susceptibility. We set out to perform a large-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…In controls and in the remaining ALS cases, repeat length was variable ranging from 5 to 13. Similar to previous findings [38,40], the most frequent alleles consisted of either 7 or 8 repeats, with respective allele frequencies being 26.1% and 67.4% in ALS patients, and 7.7% and 73.1% in controls.…”
Section: Repeat Expansions In C9orf72 Atxn2 and Nipa1 Genessupporting
confidence: 90%
“…In controls and in the remaining ALS cases, repeat length was variable ranging from 5 to 13. Similar to previous findings [38,40], the most frequent alleles consisted of either 7 or 8 repeats, with respective allele frequencies being 26.1% and 67.4% in ALS patients, and 7.7% and 73.1% in controls.…”
Section: Repeat Expansions In C9orf72 Atxn2 and Nipa1 Genessupporting
confidence: 90%
“…Of the genes in this region, certain pathogenic variants in the NIPA1 gene causes an autosomal dominant form of spastic paraplegia and triplet repeat expansion within this gene is associated with a higher risk for amyotrophic lateral sclerosis [6,7]. Haploinsufficiency of this gene has not been reported to cause these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions can range from approximately 320 kb to 500 kb, though all four genes within this 320-kb region are highly conserved and, when disturbed, are associated with or cause neurological, motor, intellectual, and behavioral problems. For example, specific missense variants of the NIPA1 (non-imprinted in PWS/AS 1; OMIM # 608145) gene are known to cause autosomal dominant hereditary spastic paraplegia and postural disturbance; repeat expansions have recently been associated with amyotrophic lateral sclerosis [6,7]. The NIPA1 protein is known to mediate magnesium transport and is highly expressed in the brain [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 15 years studies (genomewide association studies and others) have identified genetic risk factors for SALS at almost an exponential pace. We now know that polymorphisms and repeat expansions in genes like unc13a, NEK1, KIF5a, ATXN2 and NIPA1 are associated with ALS [62][63][64][65]. Interestingly, as studies in SALS are getting larger and therefore have the statistical power to analyze genetic variants with lower frequencies, overlap between FALS and SALS is emerging.…”
Section: Geneticsmentioning
confidence: 99%